- Tables, Graphs, Functions and Sequences
- Home
- Making a table and plotting points given a unit rate
- Graphing whole number functions
- Function tables with two-step rules
- Writing a function rule given a table of ordered pairs: One-step rules
- Graphing a line in quadrant 1
- Interpreting a line graph
- Finding outputs of a one-step function that models a real-world situation
- Finding outputs of a two-step function with decimals that models a real-world situation
- Writing and evaluating a function that models a real-world situation: Basic
- Graphing ordered pairs and writing an equation from a table of values in context
- Writing an equation and drawing its graph to model a real-world situation: Basic
- Identifying independent and dependent quantities from tables and graphs
- Finding the next terms of an arithmetic sequence with whole numbers
- Finding the next terms of a geometric sequence with whole numbers
- Finding patterns in shapes

# Writing a function rule given a table of ordered pairs: One-step rules Online Quiz

Following quiz provides Multiple Choice Questions (MCQs) related to **Writing a function rule given a table of ordered pairs: One-step rules**. You will have to read all the given answers and click over the correct answer. If you are not sure about the answer then you can check the answer using **Show Answer** button. You can use **Next Quiz** button to check new set of questions in the quiz.

**Q 1 - Given the following table of ordered pairs, write a one-step function rule.**

### Answer : B

### Explanation

**Step 1:**

From the table 0 − 2 = −2; 1 − 2 = −1 and so on

**Step 2:**

Input – 2 = Output or x – 2 = y

**Step 3:**

Therefore the rule is ‘Subtract 2’ from the input to get the output.

**Q 2 - Given the following table of ordered pairs, write a one-step function rule.**

### Answer : A

### Explanation

**Step 1:**

From the table 0 × 3 = 0; 1 × 3 = 3 and so on

**Step 2:**

Input × 3 = Output or x × 3 = y

**Step 3:**

Therefore the rule is ‘Multiply by 3’ the input to get the output.

**Q 3 - Given the following table of ordered pairs, write a one-step function rule.**

### Answer : C

### Explanation

**Step 1:**

From the table 0 + 3 = 3; 2 + 3 = 5 and so on

**Step 2:**

Input + 3 = Output or x + 3 = y

**Step 3:**

Therefore the rule is ‘Add 3’ to the input to get the output.

**Q 4 - Given the following table of ordered pairs, write a one-step function rule.**

### Answer : D

### Explanation

**Step 1:**

From the table 0 − 3 = −3; 1 − 3 = −3 and so on

**Step 2:**

Input – 3 = Output or x – 3 = y

**Step 3:**

Therefore the rule is ‘Subtract 3’ from the input to get the output.

**Q 5 - Given the following table of ordered pairs, write a one-step function rule.**

### Answer : A

### Explanation

**Step 1:**

From the table 0 × 5 = 0; 1 × 5 = 5 and so on

**Step 2:**

Input × 5 = Output or x × 5 = y

**Step 3:**

Therefore the rule is ‘Multiply by 5’ the input to get the output.

**Q 6 - Given the following table of ordered pairs, write a one-step function rule.**

### Answer : C

### Explanation

**Step 1:**

From the table 0 ÷ 5 = 0; 5 ÷ 5 = 1 and so on

**Step 2:**

Input ÷ 5 = Output or x ÷ 5 = y

**Step 3:**

Therefore the rule is ‘Divide by 5’ the input to get the output.

**Q 7 - Given the following table of ordered pairs, write a one-step function rule.**

### Answer : B

### Explanation

**Step 1:**

From the table 0 − 1 = −1; 1 − 1 = 0 and so on

**Step 2:**

Input – 1 = Output or x – 1 = y

**Step 3:**

Therefore the rule is ‘Subtract 1’ from the input to get the output.

**Q 8 - Given the following table of ordered pairs, write a one-step function rule.**

### Answer : D

### Explanation

**Step 1:**

From the table 0 × 6 = 0; 1 × 6 = 6 and so on

**Step 2:**

Input × 6 = Output or x × 6 = y

**Step 3:**

Therefore the rule is ‘Multiply by 6’ the input to get the output.

**Q 9 - Given the following table of ordered pairs, write a one-step function rule.**

### Answer : C

### Explanation

**Step 1:**

From the table 0 ÷ 4 = 0; 4 ÷ 4 = 1 and so on

**Step 2:**

Input ÷ 4 = Output or x ÷ 4 = y

**Step 3:**

Therefore the rule is ‘Divide by 4’ the input to get the output.

**Q 10 - Given the following table of ordered pairs, write a one-step function rule.**

### Answer : A

### Explanation

**Step 1:**

From the table 0 − 3 = −3; 1 − 3 = −3 and so on

**Step 2:**

Input – 3 = Output or x – 3 = y

**Step 3:**

Therefore the rule is ‘Subtract 3’ from the input to get the output.